1996
DOI: 10.1002/(sici)1097-0010(199608)71:4<459::aid-jsfa602>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Release of 14C‐Labelled Phenolic Groups from Intact Dietary Spinach Cell Walls During Passage Through the Rat Intestine

Abstract: Feruloyl and p-coumaroyl groups in spinach cell walls (CW) were labelled using [14C]cinnamic acid and fed to rats. In the caecum and colon, ferulic acid (FA) and p-coumaric acid (PCA) were released from the CW. Few feruloyl or coumaroyl groups remained in the CW to be excreted in faeces, and thus the presence of simple phenol-sugar esters provided little protection of the polysaccharides to enzymic attack. Some oxidatively coupled phenols were also released but a portion remained in the CW. The oxidatively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 0 publications
1
43
0
4
Order By: Relevance
“…As illustrated in Fig. 5, 5-CQA, which is stable when incubated with gastric juice (Rechner et al, 2001), and the other CQAs are probably subjected to the action of esterases in the wall of the small intestine (Buchanan et al, 1996;Andreasen et al, 2001), releasing caffeic acid that is converted to caffeic acid-3-O-sulfate which then enters the bloodstream. It is possible that 3-and 4-CQAL, which appear as sulfates in plasma, could also be hydrolyzed in the small intestine and contribute to the caffeic acid pool.…”
Section: Bioavailability Of Coffee Chlorogenic Acids In Humansmentioning
confidence: 99%
“…As illustrated in Fig. 5, 5-CQA, which is stable when incubated with gastric juice (Rechner et al, 2001), and the other CQAs are probably subjected to the action of esterases in the wall of the small intestine (Buchanan et al, 1996;Andreasen et al, 2001), releasing caffeic acid that is converted to caffeic acid-3-O-sulfate which then enters the bloodstream. It is possible that 3-and 4-CQAL, which appear as sulfates in plasma, could also be hydrolyzed in the small intestine and contribute to the caffeic acid pool.…”
Section: Bioavailability Of Coffee Chlorogenic Acids In Humansmentioning
confidence: 99%
“…The active compounds -including caffeic acid, ferulic acid, and p-coumaric acid -are commonly present as ester conjugates in plants (Figure 2). Humans depend on the gut microbiome for the cinnamoyl esterases required to cleave these ester linkages, which explains why the caffeoyl, feruloyl, and p-coumaroyl groups exist in esterified form in the proximal gut, but as free acids in the colon (12,13). Members of Bifidobacterium, Lactobacillus, and Escherichia in the human gut have been experimentally shown to hydrolyze esters of caffeic acid and ferulic acid (11); however, this activity is likely more widespread, as many bacteria and fungi produce cinnamoyl esterases (14).…”
Section: Direct Microbial Interference With Xenobioticsmentioning
confidence: 99%
“…The gastrointestinal tract houses the most numerous microbial community (the gut microbiota), consisting of approximately 10 13 microbial cells (1). Collectively, the aggregate genomes of the gut microbiota encode more than 100 times as many unique genes as the approximately 20,000 protein-coding genes found in the human genome and nearly 20,000 gene families (2).…”
Section: Introductionmentioning
confidence: 99%
“…There was evidence for the removal of free phenolic acids from the gut (presumably by absorption into the body tissues) and for the accumulation in the gut contents of chromatographically-immobile material, much of which survived passage through the gut to be excreted in faeces. Phase-partitioning of the soluble material in the gut contents suggested that hydrophilic (sugar-associated) 14C-labelled phenolics are released from the CW and subsequently become less hydrophilic, presumably as sugar groups are removed (Buchanan et al 1996).…”
Section: Digestion Of Primary-cell-wall Phenolicsmentioning
confidence: 99%